2010
DOI: 10.1007/s12603-010-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Scurvy in hospitalized elderly patients

Abstract: Ninety-four percent of patients with clinical symptoms of scurvy had vitamin C deficiency. Our results suggest that in hospitalized elderly patients, clinical symptoms allow scurvy diagnosis. Scurvy could be a frequent disease in elderly patients admitted to acute geriatric ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…Unfortunately, multiple recent publications have demonstrated scurvy and vitamin C deficiency in developed countries. [33][34][35] Nancy Strange presented a case study at SAWC, 2012, where data from the Indiana University School of Medicine, IU Health, Indianapolis, found that 14 of 15 individuals with delayed wound healing had ascorbic acid levels below normal ranges. 36 One case was present in the state of Florida, known for its large production of citrus fruit.…”
Section: Occurrence Of Micronutrient Deficiency In the Elderlymentioning
confidence: 99%
“…Unfortunately, multiple recent publications have demonstrated scurvy and vitamin C deficiency in developed countries. [33][34][35] Nancy Strange presented a case study at SAWC, 2012, where data from the Indiana University School of Medicine, IU Health, Indianapolis, found that 14 of 15 individuals with delayed wound healing had ascorbic acid levels below normal ranges. 36 One case was present in the state of Florida, known for its large production of citrus fruit.…”
Section: Occurrence Of Micronutrient Deficiency In the Elderlymentioning
confidence: 99%
“…Во всех этих случаях у больных имелись фак-торы риска дефицита витамина С, такие, как пожи-лой возраст, алкоголизм, психические заболевания, низкий уровень доходов, способствующие, особен-но в случае одинокого проживания, неполноценно-му питанию; хронические заболевания кишечника и состояния с повышенной потребностью в витами-не С; диета с исключением фруктов из-за пищевой аллергии. Ретроспективный анализ 12 случаев цин-ги, диагностированных в клинике Mayo с 1976 по 2002 годы в США [8] и проспективное исследование 18 пожилых госпитализированных больных цингой во Франции [22], свидетельствуют, что при диффе-ренциальной диагностике пурпуры или спонтанных кожных кровоизлияний у пациентов из этих групп риска следует помнить о цинге и внимательно из-учать пищевой анамнез.…”
Section: Discussionunclassified
“…Using vitamin C to treat cancer patients is not just a question of whether a high concentration of vitamin C might kill cancer cells. There is evidence that a substantial proportion of hospital patients have a vitamin C deficiency [24,25]. Therefore, vitamin C may be beneficial for some hospital patients with or without cancer [26,27].…”
Section: Sub-clinical Doses Of Otherwise Effective Therapiesmentioning
confidence: 99%